Ultrathin High Surface Area Nickel Boride (NixB) Nanosheets as Highly Efficient Electrocatalyst for Oxygen Evolution. Issue 17 (10th May 2017) - Masa, Justus; Sinev, Ilya; Mistry, Hemma; Ventosa, Edgar; de la Mata, Maria; Arbiol, Jordi; Muhler, Martin; Roldan Cuenya, Beatriz; Schuhmann, Wolfgang
Abstract : The overriding obstacle to mass production of hydrogen from water as the premium fuel for powering our planet is the frustratingly slow kinetics of the oxygen evolution reaction (OER). Additionally, inadequate understanding of the key barriers of the OER is a hindrance to insightful design of advanced OER catalysts. This study presents ultrathin amorphous high‐surface area nickel boride (Ni x B) nanosheets as a low‐cost, very efficient and stable catalyst for the OER for electrochemical water splitting. The catalyst affords 10 mA cm −2 at 0.38 V overpotential during OER in 1.0m KOH, reducing to only 0.28 V at 20 mA cm −2 when supported on nickel foam, which ranks it among the best reported nonprecious catalysts for oxygen evolution. Operando X‐ray absorption fine‐structure spectroscopy measurements reveal prevalence of NiOOH, as well as Ni‐B under OER conditions, owing to a Ni‐B core@nickel oxyhydroxide shell (Ni‐B@NiO x H) structure, and increase in disorder of the NiO x H layer, thus revealing important insight into the transient states of the catalyst during oxygen evolution. Abstract : Ultrathin high‐surface area nickel boride nanosheets supported on nickel foam show outstanding activity in catalyzing the oxygen evolution reaction, ranking among the best nonprecious catalysts for oxygen evolution reported to date.